Structure changes, the contribution of sectors, income per capita Indonesia in 1990 – 2014 - Paulina Harun (Universitas Hayam Wuruk Perbanas, 2016)
Economic development is seen as a process of transition from one phase to another, from simple economic structure (agriculture) to the modern economy structure. Economic development is characterized by changes in the structure of the agricultural sector into the modern sector. The changes affect all the matters related thereto. Therefore, a change or transformation of economic activity is referred to as a structural change. This study aims to analyze the structural changes in the national product, and the factors that cause changes in the structure and level of sectoral imbalances as a result of the structural changes. The study was conducted by using the economic sector, divided into four major groups, namely the primary, secondary, utilities and services from 1990 to 2014. Secondary data were collected by the method of sectoral trends, models Chanery Syrquin-Barua, Theil index. The results showed that the sectoral trend has a positive result such as utilities and services sectors, while the primary and secondary sectors tend to be negative. From the model Chenery, Syrquin-Barua shows the per capita income has a positive effect on the primary sector and the utilities, residents have positive effect on the secondary sector, utilities and services. Meanwhile dummy variable has a positive effect on the primary sector, secondary and services. Sectoral inequality occurs in the secondary sector.